Metavirome analysis of domestic sheep in Shaanxi, Gansu, and Ningxia, China - Zhang, Sinong; Gao, Hui; Zhang, Gang; Fang, Min; Kong, Yunyi; Jiang, Lingling; Liu, Qiang; Wang, Pu; Liu, Yanling; Li, Yong (Frontiers in Veterinary Science, 2024)
Sheep play an important role in China’s agricultural development, but they are also potential hosts for many viruses, some of which have been identified as zoonotic pathogens, which may pose a serious threat to social public health and animal husbandry. Therefore, clarifying the characteristics of viruses in sheep will provide an important basis for the study of pathogenic ecology and viral evolution of viruses carried by sheep. We collected nasal and anal swabs from 688 sheep in 22 counties in Shaanxi, Gansu, and Ningxia, China, between January 2022 and July 2023, and utilized next-generation sequencing technology and bioinformatics approaches to identify the viruses in the samples. A total of 38 virus families carried by sheep were identified, including 12 ssRNA (+) virus families, 2 dsRNA virus families, 8 ssDNA (+) virus families, and 18 dsDNA virus families. Among them, Astroviridae, Coronaviridae, Picornaviridae, and Tobaniviridae in RNA virus families and Herpesviridae, Adenoviridae, and Circoviridae in DNA virus families are all viruses that are frequently detected in most ruminants. Alpha and beta diversity results showed that there was no difference in the overall richness and diversity of RNA and DNA viruses among the three provinces (p > 0.05). The evolutionary analysis demonstrated a tight link between the viral members carried by sheep and other ruminant viruses, implying that these viruses may spread across different species of ruminants. This study established a library of RNA and DNA viruses carried by sheep in the Shaanxi-Gansu-Ningxia region, providing an overview of the viruses present in this population. The findings offer valuable data for further research on virus evolution and monitoring in sheep.